Incendios forestales, pastoreo, impacto ganadero, montaña mediterránea, SIG, Pirineo. - Vicente Serrano, Sergio M.; Lasanta Martínez, Teodoro; Cuadrat Prats, José M. (Geographicalia, 2016)
The study concerns the impact of livestock on the fire-risk evolution in Borau valley (Pyrenees) between 1957 and 2000. The risk has grown considerably due to an increase in pine woods and scrub areas because of land abandonment and livestock extensification. The decrease in livestock pression has been crucial in the potential firerisk increase. The decline of stay sheep and the extensification of their shepherding areas have been the most important factors in the process.
Keywords: Fire forest; livestock impact; mediterranean mountains; GIS; Pyrenees.